The effect of a word processor as an accommodation for students with learning disabilities - Berger, Cassie L.; Lewandowski, Larry (Journal of Writing Research, 2013)
The effects of writing format (handwritten (HW) versus word processor (WP)) were examined in a sample of college students with and without learning disabilities (LD). All students wrote two essays, one in each format, scored for quality and length. Groups did not differ in age, gender, ethnicity, mathematical calculation, writing fluency, essay length or essay quality. The "interaction hypothesis" was not supported, in that the use of a word processor as a writing accommodation did not provide a differential boost to students with LD. Both groups produced longer essays in the WP versus HW condition. The best predictor of essay quality was essay length regardless of writing format. Most students in each group preferred the WP format. Interestingly, a smaller percentage of students in the LD group (72%) than NLD group (91%) used the available time for writing.Keywords: accommodations, learning disabilities, college students, writing, word processor